A one-pot, three-component aminotriazine annulation onto 5-aminopyrazole-4-carbonitriles under microwave irradiation - Lim, Felicia Phei Lin; Luna, Giuseppe; Dolzhenko, Anton (Pergamon, 2015)
A one-pot, three-component, microwave-assisted reaction of 5-aminopyrazole-4-carbonitriles, triethyl orthoformate and cyanamide afforded novel 7-arylamino-substituted 4-aminopyrazolo[1,5-a][1,3,5]triazine-8-carbonitriles. The reaction proceeded in a chemo- and regioselective manner resulting in the successful amino-1,3,5-triazine annulation onto 5-aminopyrazole-4-carbonitriles to give 4-aminopyrazolo[1,5-a][1,3,5]triazine-8-carbonitriles. The operational simplicity of the method and high purity of the products, which can be isolated via simple filtration, make this approach attractive for the preparation of a library of compounds for drug discovery processes.